An efficient method for subcutaneous veins localization using Near Infrared imaging - Shahzad, A. (IEEE Computer Society, 2014)
In the majority of the medical treatments, intravenous catheterization is the most important phase in which skilled medical practitioners locate the best vein and perform catheterization process for medication or blood sampling. Due to the different physiological characteristics, mainly darker skin tone, scars or dehydrated condition of patients, medical staff stumbles in localization of veins. This paper proposes an enhanced method which intends to overcome the difficulty faced by medical staff in veins localization for intravenous catheterization. Using the Near Infrared imaging and image processing algorithms a novel approach for veins visualization is proposed. In order to have complete insight of veins location in the subcutaneous layer of skin a method to estimate the depth of veins using Monte Carlo simulations is presented. The complete system will increase guidance towards medical practitioners to facilitate the insertion of catheter or syringe into the veins. Â© 2014 IEEE.